PENGARUH MARKETING MIX DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN MENGIKUTI KURSUS DI LPK PROGRESS PARE Oleh : - Dian Ruhamak (Universitas Islam Balitar, 2016)
The purpose of this study was to analyze the factors that influenceconsumer decisions through the marketing mix and consumer attitudes towarddecisions follow a course in progress pare LPK, to see the extent to whichdecisions are taken through the marketing mix and the attitude towards thedecision to follow a course in progress pare LPK. Descriptive analysis showedthat the marketing mix variables (price, place, product, promotion, people,physical environment and processes) and consumer attitudes positive influenceon the decision to follow the course. Based on the research results, thehypothesis 1 which states, thought to have a positive pegaruh between factors(price, place, product, promotion, people, physical environment and processes)and consumer attitudes positive influence on the decision to follow a course inprogress pare LPK